Physical quantities, dimensions and units of measurement in mathematical packages - Ochkov, V.F.; Lehenkiy, V.I.; Minaeva E.A. (Математичні машини і системи, 2009)
There are described problems and solutions when working with valid dimensions in the medium of mathematical program (engineer calculator) Mathcad.